Bladder tumor recurrence after urothelial carcinoma of the upper urinary tract - Lonergan, Peter E. (Transl Androl Urol, 2020)
Upper tract urothelial carcinoma (UTUC) is a relatively uncommon and poorly investigated malignancy, however, bladder recurrence after radical nephroureterectomy (RNU) is a frequent event. In this review, we summarize the current knowledge on risk prediction of bladder tumor recurrence after RNU, including surgical strategies and adjuvant intravesical treatments to reduce the risk of recurrence. Finally, we outline some of the more recent advances in genomics that will likely lead to new prognostic markers and risk stratification tools that may refine UTUC treatment in the future.